The Impact of Ethics, Trust and User Experience Mediating Variables on the Corporate Image of Bank Syariah Indonesia KC Palangkaraya - Rafii, Mohamad (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the context of digital marketing of Bank Syariah Indonesia KC Palangkaraya, this study investigates the influence of ethics, trust, and user experience on corporate image. PLS-SEM (Partial Least Squares Structural Equation Modeling), implemented with Smart-PLS version 3.2.7, was the quantitative methodology used. The research sample consisted of one hundred randomly selected people. The results showed that trust has the most significant influence on corporate image (path coefficient 0.387, p-value 0.001). Ethics, on the other hand, has a positive but statistically insignificant effect (path coefficient 0.145, p-value 0.289). In addition, user experience has a significant effect on corporate image (path coefficient 0.282, p-value 0.007). However, user experience does not serve as a moderator in the relationship between ethics and trust in corporate image. This study suggests that Bank Syariah Indonesia should prioritize building customer trust, providing an ideal user experience, and applying ethical principles in digital marketing to improve its corporate image.